Creative Packaging Design for Products - Borja-Galeas, Carlos (2022)
The packaging is part of the final product and its ergonomic design becomes a purchase motivator. They fulfill different functions, such as: protector, conservator and provides logistical security of the product, among others. The use of technological tools as a transforming element in digitization, printing and prototyping accelerates the process and significant savings are achieved in the use of materials. In the prototyping stage, it is designed according to the product and different methodologies are used, such as participatory design and design thinking, before its construction. The objective of this research is to present the experience of higher education students in the design of prototypes using disruptive tools focused on the construction of packaging. 18 graphic design students participated, who managed to generate 3 prototypes, which were tested by direct observation in the Gesell chamber with 5 children with disabilities, 8 early childhood teachers and 8 parents separated into groups due to similarity. Digital modeling and the use of ecological substrates (earth pact) with their own colors and diverse textures, friendly to the environment, generated an appeal to the end user prior to production. The use of lasers in the die cutting process creates an attractive color effect (dark beige) by burning the paper. In the future, the aim is to work with other substrates (papers and cardboard) that allow measuring durability and malleability (if it can be easily bent without being damaged).